Analysis of Knowledge about Early Mobilization in Stroke Patients - Sujatmiko (Health and Technology Journal (HTechJ), 2024)
Stroke sufferers have problems meeting basic needs, one of which is related to mobilization. The mobilization mechanism for stroke sufferers has its mechanism, so there must be guidance. This research aims to analyze the level of knowledge of stroke patients regarding early mobilization. This research has a descriptive-analytical design using 25 patient respondents. The measuring tool used is a knowledge questionnaire on early mobilization in stroke patients. The results obtained were that most of the respondents' knowledge level was Poor (36%). Poor or not optimal knowledge can be caused by the client not being ready because, for patients a stroke is a sudden and sudden illness. Several other studies suggest that early mobilization is important in improving the patient's healing process. Early mobilization of stroke patients is an important strategy in the rehabilitation of respondents. This involves starting physical activity as soon as possible after a stroke to promote recovery of body function, reduce the risk of complications, and improve the patient's overall quality of life.